Small and Medium-Sized Businesses as a Factor Influencing the Level of Employment - Aynura Hajiyeva; Amaliya Hajiyeva; Kifayat Khudaverdiyeva; Nigar Nigar (Australasian Accounting Business and Finance Journal, 2024)
SMEs are vital for socio-economic development, driving employment and innovation. They contribute over 70% of jobs in developed countries and play a key role in shaping gross domestic product. The purpose of the article is to analyze employment in small and medium-sized enterprises and to develop ways to increase it. To achieve the goal, statistical analysis, synthesis, comparison, generalization, abstraction, and formalization were used. The article compared criteria for enterprise distribution in Azerbaijani legislation and the OECD, evaluated macroeconomic indicators of SMEs in Azerbaijan, analyzed employment dynamics by economic activity and region, and proposed mechanisms for self-employment in both the general economy and SMEs. As a result of the research, the mechanism of self-employment of the unemployed population in the economic districts of Azerbaijan, which consists of five stages, was constructed. The main issue in this case is a business idea created by the team, determining the amount of necessary resources, creating the product, and determining risks. The practical significance of the results obtained is that the proposed mechanism of self-employment of the unemployed population in the economic regions of Azerbaijan can be implemented in the development of state programmes.
Keywords: venture investment; business project; labour market; added value; government support.